MENGEKSPLORASI JARINGAN KONSEPTUAL DALAM EKONOMI SIRKULAR: ANALISIS BIBLIOMETRIK - Afnei Ngan Billy Tumba (Fakultas Bisnis Universitas Kristen Duta Wacana, 2024)
ABSTRACT Organizations that adopt the tenets of a circular economy tend to demonstrate enhanced innovation in creating environmentally conscious products and services, coupled with elevated competitiveness in global markets. The concept of a circular economy is becoming an increasingly relevant topic in future planning for both academic and commercial practice, as global sustainability challenges garner increasing attention. This study aims to conduct a bibliometric analysis of the literature on the circular economy. The sample for this study was collected from the Web of Science database, focusing on publications between 2013 and 2024, yielding 346 documents from 157 sources. This research employs a bibliometric analysis, utilizing co-occurrence, co-citation, and co-word techniques. The findings of this study offer a more comprehensive understanding of the literature on the circular economy, business models, green innovation, and economic impact. This research concludes that the large nodes for “circular economy” and “business model innovation” in the analysis indicate that integrating innovative business models is a key element in the circular economy. Keywords: Circular Economy; Business Model; Green Innovation; Economic Impact; Bibliometric Analysis ABSTRAK Perusahaan yang merangkul gagasan ekonomi sirkular biasanya menunjukkan peningkatan inovasi dalam pengembangan barang dan jasa yang ramah lingkungan, serta peningkatan daya saing di pasar global. Ekonomi sirkular menjadi topik yang relevan dalam perencanaan kedepannya bagi akademis dan praktik komersial karena tantangan keberlanjutan global semakin mendapat perhatian. Tujuan penelitian ini adalah menganalisis literatur tentang ekonomi sirkular menggunakan metode bibliometrik. Sample dalam penelitian ini mengumpulkan data dari basis data Web of Science dengan fokus publikasi antara tahun 2013 sampai 2024 dengan 346 dokumen dari 157 sumber. Metode penelitian ini menggunakan analisis bibliometrik dengan teknik analisis seperti co-occurrence, co-citation, dan co-word. Hasil dari penelitian ini memberikan pemahaman yang lebih baik terkait literatur ekonomi sirkular, model bisnis, inovasi hijau, dan dampak ekonomi. Kesimpulan dari penelitian ini adalah Node yang besar untuk